Selection Combiner in Time-Varying Amplify Forward Cooperative Communication - Ong, Sylvia; Zen, Hushairi (International Journal of Integrated Engineering, 2020)
This research presents the diversity combining schemes for Multiple Symbol Double Differential Sphere Detection (MSDDSD) in a time-varying amplify-and-forward wireless cooperative communication network. Four diversity combiners, including direct combiner, Maximal Ratio Combiner (MRC), semi MRC and Selection Combiner (SC) are demonstrated and explained in details. A comprehensive error probability and outage probability performance analysis are carried through the flat fading Rayleigh environment for semi MRC and SC. Specifically, error performance analysis is obtained using the PDF for SC detectors. Finally, power allocation expression based on error performance minimization approach is presented for the proposed SC performance optimization. It is observed that the performance analysis matches well with the simulation results. Furthermore, the proposed SC scheme offers better performance among the conventional MRC and direct combiner schemes in the presence of frequency offsets.